Structure-Based Scaffold Repurposing for G Protein-Coupled Receptors: Transformation of Adenosine Derivatives into 5HT(2B)/5HT(2C) Serotonin Receptor Antagonists - Tosh, Dilip K. (J Med Chem, 2016)
Adenosine derivatives developed to activate adenosine receptors (ARs) revealed µM activity at serotonin 5HT(2B) and 5HT(2C) receptors (5HTRs). We explored the SAR at 5HT(2)Rs and modeled receptor interactions in order to optimize affinity and simultaneously reduce AR affinity. Depending on N(6) substitution, small 5′-alkylamide modification maintained 5HT(2B)R affinity, which was enhanced upon ribose substitution with rigid bicyclo[3.1.0]hexane (North (N)-methanocarba), e.g. N(6)-dicyclopropylmethyl 4′-CH(2)OH derivative 14 (K(i) 11 nM). 5′-Methylamide 23 was 170-fold selective as antagonist for 5HT(2B)R vs. 5HT(2C)R. 5′-Methyl 25 and ethyl 26 esters potently antagonized 5HT(2)Rs with moderate selectivity in comparison to ARs; related 6-N,N-dimethylamino analogue 30 was 5HT(2)R-selective. 5′ position flexibility of substitution was indicated in 5HT(2B)R docking. Both 5′-ester and 5′-amide derivatives displayed in vivo t(1/2) of 3–4 h. Thus, we used GPCR modeling to repurpose nucleoside scaffolds in favor of binding at nonpurine receptors, as novel 5HT(2)R antagonists, with potential for cardioprotection, liver protection or CNS activity.